The association between the utilization of SGLT2 inhibitors and diabetic retinopathy; a systematic review and meta-analysis of cohort studies - Shahriar Barkhordari; Shahrzad Ghaffariyan; Farzin Banei; Mohammad Shirvani; Farangis yazdanjou; Sara Ghaseminejad Kermani; Mohammad Akbari; Alireza Baghaei; Mobin Mohammadtabar (Journal of Nephropharmacology)
Introduction: Diabetic retinopathy is one of the principal causes of blindness globally. The impact of sodium-glucose cotransporter 2 (SGLT-2) inhibitors, a category of anti-diabetic medications, on diabetic retinopathy remains undetermined. Consequently, this study aimed to examine the association between the utilization of SGLT2 inhibitors and the incidence of diabetic retinopathy. Materials and Methods: This investigation systematically searched databases, including Web of Science, Cochrane, ProQuest, PubMed, and Google Scholar, until March 7, 2024. A systematic review and meta-analysis methodology was employed. Data were analyzed using STATA software version 14, considering a significance level of tests at P<0.05. Results: The application of SGLT2 inhibitors was connected with a diminished diabetic retinopathy risk (odds ratio [OR]: 0.77, 95% CI: 0.69, 0.86). Among women, SGLT2 inhibitor use did not notably influence diabetic retinopathy risk (OR: 0.84, 95% CI: 0.69, 1.03). However, among men, employing SGLT2 inhibitors decreased the risk (OR: 0.81, 95% CI: 0.71, 0.92). In comparison to dipeptidyl peptidase-4 inhibitors (OR: 0.70, 95% CI: 0.53, 0.94) and pioglitazone (OR: 0.75, 95% CI: 0.74, 0.76), SGLT2 inhibitors lowered the risk of diabetic retinopathy. However, when compared to sulfonylureas (OR: 0.45, 95% CI: 0.17, 1.17) and GLP1-RA (OR: 0.70, 95% CI: 0.42, 1.17), SGLT2 inhibitors did not notably affect diabetic retinopathy. Moreover, using SGLT2 inhibitors in the age groups of 50-54 years (OR: 0.74, 95% CI: 0.55, 0.98), 55-59 years (OR: 0.65, 95% CI: 0.53, 0.79), and 60-64 years (OR: 0.89, 95% CI: 0.82, 0.97) was linked to lower diabetic retinopathy risk. Nevertheless, in the 65-69 age group, SGLT2 inhibitor administration did not significantly alter the diabetic retinopathy risk (OR: 1.04, 95% CI: 0.94, 1.15). Conclusion: The intake of SGLT2 inhibitors has been linked to a diminution in the hazard of diabetic retinopathy. However, further research in this domain is recommended, given the need for studies examined. Registration: This study has been compiled based on the PRISMA checklist, and its protocol was registered on the PROSPERO (CRD42024523959) and Research Registry (UIN: reviewregistry1808) website.